2008
DOI: 10.1177/0961203308090025
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic role of antiphospholipid antibodies

Abstract: The antiphospholipid antibody syndrome (APS) is characterized by recurrent arterial and venous thrombosis and/or pregnancy in association with antiphospholipid (aPL) antibodies. The pathogenic mechanisms in APS that lead to in vivo injury are incompletely understood. Recent evidence suggests that APL antibodies alter regulation of haemostasis and induce activation of complement. We will discuss the current knowledge on how aPL antibodies trigger increased inflammation and enhanced thrombotic tendency, and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
4

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 55 publications
0
66
0
4
Order By: Relevance
“…The frequent finding of thrombocytopenia and thrombosis in patients with APS suggests that aPLs interact with platelets in a manner that triggers platelet aggregation and thrombosis (9,18,19) . The mechanism of thrombosis in patients with aPLs is still unknown (3) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequent finding of thrombocytopenia and thrombosis in patients with APS suggests that aPLs interact with platelets in a manner that triggers platelet aggregation and thrombosis (9,18,19) . The mechanism of thrombosis in patients with aPLs is still unknown (3) .…”
Section: Discussionmentioning
confidence: 99%
“…Chart 2 -Manifestations of antiphospholipid syndrome (6,7) mechanisms; binding and activation of platelets; interaction with endothelial cells; induction of the expression of adhesion molecules and tissue factor; as well as activation of the complement cascade (6,9,18) . Perinatal APS is rare and manifests in infants born to mothers with APS or positive aPL tests.…”
Section: • Erythematous Maculesmentioning
confidence: 99%
“…However, the aPL have been implicated in reactions that interfere with almost all known haemostatic and endothelial cell reactions [2]. Furthermore, some evidence for an effect of aPL on the complement system has been described and related with pregnancy complications and thrombosis [3]. Given the heterogeneity of clinical manifestations in APS, it is likely that more than one pathophysiological process may play a role.…”
Section: Introductionmentioning
confidence: 99%
“…aPLA antibodies are directed against plasma proteins bound to anionic phospholipids [2]. Research has shown that aPLA-associated vascular lesions are predominantly noninflammatory vessel alterations with thrombotic luminal obliteration [2][3][4][5][6]. Thrombotic microangiopathy (TMA), which is histologically defined as the development of hyaline thrombi in small vessels, is a frequent finding in patients with thrombotic thrombocytopenic purpura (TTP) and hemolytic uremic syndrome (HUS).…”
Section: Introductionmentioning
confidence: 99%
“…aPLA antibodies are directed against plasma proteins bound to anionic phospholipids [2]. Research has shown that aPLA-associated vascular lesions are predominantly noninflammatory vessel alterations with thrombotic luminal obliteration [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%